Raspberry painting on the wall of the Yellowknife Inn ... - Campbell, Sandy (University of Alberta Library, 2015)
The south wall of the Yellowknife Inn faces a parking lot at 50th Street and 50th Avenue. The Urban Art in Yellowknife exhibit includes cut-out paintings of birds and wild plants that produce edible berries. This painting is of the raspberry and shows the foliage and the green and ripe berries. The sign below shows the name of the plant in ten different languages. ...